2017
DOI: 10.15586/jrenhep.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels are Associated with Liver Disease Severity in Patients with Cirrhosis

Abstract: Vitamin D deficiency is common in advanced liver disease but its clinical significance remains controversial. The aim of this study was to examine the correlation of 25-hydryoxyvitamin D levels with liver disease severity and calcium levels in adults with cirrhosis. This cross-sectional study included 180 adults with cirrhosis enrolled in a clinical cohort study at a single university hospital. The mean age was 58.8 (±9.2) years, and cirrhosis was attributed to alcohol use in 27.2%, hepatitis C in 35.0%, non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Choubey and Ratlamwala [101] had higher number of Male patients (72%) than females (28%). In the study by Rech MA et al, [18] 53.3% patients were males [8] . Gupta et al [19] reported that 91% were male and 9% were female.…”
Section: Gendermentioning
confidence: 89%
See 1 more Smart Citation
“…Choubey and Ratlamwala [101] had higher number of Male patients (72%) than females (28%). In the study by Rech MA et al, [18] 53.3% patients were males [8] . Gupta et al [19] reported that 91% were male and 9% were female.…”
Section: Gendermentioning
confidence: 89%
“…Choubey and Ratlamwala [17] had majority of patients (52%) were in age group 41-60 years followed by 21-40 years (30%). The mean age of patients in a study by Rech MA et al [18] was 58.8±9.2 years. Gupta et al [19] reported that mean age of the patients was 46.05±11.31years.…”
Section: Agementioning
confidence: 90%
“…This study shows that total 25(OH)D levels correlate inversely with liver disease severity in adults with cirrhosis, while no correlation exists between 25(OH)D levels and albumin-corrected serum calcium levels. 12 On classifying patients (N=200 Certain limitation of the study was that sample size was small and we have not followed patients after supplementation of vitamin D. After completion of my study so we were not able to know impact of correction of vitamin D level in patients with chronic liver disease, which required further long term and large sample size study…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in 180 patients with cirrhosis study done by Rech et al; they found no association of lower vitamin D level with increasing age and female sex but significant association with albumin, PT-INR, bilirubin and alcohol etiology. 22 Finkelmeier et al reported that patients with severe 25(OH) D3 deficiency had the highest mortality risk (hazard ratio 2.225, p=0.002). 21 These results suggest that vitamin D might be both a biomarker of severity and a potential therapeutic target in CLD.…”
Section: Discussionmentioning
confidence: 99%